Finance and Development, September 2014. (Finance and Development; Finance and Development ;, 2014)
This year, we mark the 70th anniversary of the IMF and World Bank and the 50th anniversary of F and D. The world has seen a staggering amount of change in the past seven decades. So, with these two anniversaries in mind we focused our attention on the transformation of the global economy-looking back and looking ahead. What will the global economy look like in another 70 years? Five Nobel laureates-George Akerlof, Paul Krugman, Robert Solow, Michael Spence, and Joseph Stiglitz-share their thoughts on which single 'frontier' issue promises to shape the economic landscape in the years ahead. In 'A World of Change,' Ayhan Kose and Ezgi Ozturk chart the economic transformations of the past 70 years. Martin Wolf looks at the perils and promise of globalization in 'Shaping Globalization.' IMF Chief Christine Lagarde charts a course for the IMF in the next decade in Straight Talk IMF Chief Economist Olivier Blanchard distills the lessons of the 2008 global financial crisis in 'Where Danger Lurks.' This issue also features cartoonist Nick Galifianakis and Joe Procopio telling the story of the IMF's origins in a seven-page comic. The People in Economics series profiles a giant in economics-Nobel winner and Stanford professor Ken Arrow, who built on an early passion for math and work in meteorology during World War II to launch a storied career in economics. Articles on the future of energy in the global economy by Jeffrey Ball and on measuring inequality-the most hotly debated economic issue of recent days-by Jonathan Ostry and Andrew Berg round out the package.